TPD micromolecule-based perovskite light transmission layer preparation method and perovskite cell device preparation method
By adopting the perovskite optical transport layer preparation method based on TPD small molecules in perovskite solar cells, the problem of HTL not meeting the requirements is solved, and the photoelectric conversion efficiency and stability of perovskite solar cells are improved.
Patent Information
- Application Number
- CN202411954336.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
In the prior art, the hole transport layer (HTL) in high-performance inverted perovskite solar cells does not meet the requirements, affecting the crystallization and charge transport/extraction efficiency of the perovskite layer.
The perovskite optical transport layer preparation method based on TPD small molecules is prepared, and the perovskite optical transport layer with excellent characteristics is prepared by spin coating the TPD small molecule solution and the perovskite precursor solution and annealing treatment.
The photoelectric conversion efficiency and stability of perovskite solar cells are improved, and by matching the energy levels of nickel-oxide-based hole transport layer and perovskite film, interface defects are reduced, valence band conduction bands are improved, hole extraction and electron suppression are enhanced.
Smart Images

Figure CN119730665A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solar photovoltaic technology, and in particular to a method for preparing a perovskite light transmission layer based on TPD small molecules and a method for preparing a perovskite cell device. Background Art
[0002] Perovskite has many advantages such as high extinction coefficient, high carrier mobility, low exciton binding energy and easy solution preparation. It has received widespread attention from researchers in recent years. The current certified efficiency of formal perovskite solar cells has reached 25.8%, and the certified efficiency of trans cells has exceeded 26.7%.
[0003] In perovskite cell devices, the hole transport layer (HTL) plays a key role as a p-type layer for influencing the crystallization of the perovskite layer, which is deposited on the HTL and extracting holes from the perovskite to the anode. Both organic and inorganic semiconductors are widely used as HTL in inverted PSCs. Given that the HTL is the front layer through which light passes before exciting the perovskite film, the HTL must have good transparency. In addition, the HTL is both a substrate for perovskite growth and a charge selective layer in the inverted PSC. Therefore, the properties of the HTL significantly affect the transmittance, the quality of the perovskite film, and the charge transport / extraction efficiency of the device. Therefore, the HTL in high-performance inverted PSCs must exhibit high transmittance, appropriate energy levels, high conductivity, and ideal chemical stability.
[0004] Therefore, finding a hole transport layer with simple preparation process and low cost is still one of the important issues in achieving efficient and stable preparation of perovskite solar cells. Summary of the invention
[0005] In view of the problem that the HTL in the high-performance inverted PSC in the prior art does not meet the requirements, the present invention provides a method for preparing a perovskite light transport layer based on TPD small molecules and a method for preparing a perovskite battery device, which can not only make the energy levels of the nickel oxide-based hole transport layer and the perovskite film more matched, but also improve the stability of the device while improving the photoelectric conversion efficiency of the battery device.
[0006] The present invention is achieved through the following technical solutions: A method for preparing a perovskite light transmission layer based on TPD small molecules comprises the following steps: S1, spin coating TPD small molecule solution to form a wet film, and then annealing the wet film for the first time to obtain a TPD film; S2, spin coating the perovskite precursor solution on the TPD film, followed by a second annealing to obtain a perovskite light transmission layer with TPD small molecules.
[0007] Preferably, the TPD small molecule solution is obtained by dissolving TPD powder in chlorobenzene, wherein the TPD small molecule is N,N′-diphenyl-N,N′-di(3-methylphenyl)-1,1′-biphenyl-4,4′-diamine; and the concentration of the TPD small molecule solution is 1-4 mg / ml.
[0008] Preferably, in S1, during the first annealing, the temperature is 100-150° C. and the time is 10-30 min.
[0009] Preferably, in S1, the thickness of the TPD hole transport layer is 3-8 nm.
[0010] Preferably, in S2, the perovskite precursor solution is prepared by dissolving PbI2: (CH(NH2)2I+CsI) with a molar ratio of 1:1 in a polar solvent mixed with DMSO / DMF, sealing the mixed solution, and obtaining a clear perovskite precursor solution with a concentration of 0.8~1.7M after sufficient dissolution.
[0011] Preferably, in S2, during spin coating, the volume of the added perovskite precursor solution and the area of the perovskite film are in a relationship of 9.6-11 μL / cm 2 .
[0012] Preferably, in S2, during the second annealing, the temperature is 100-150° C. and the time is 15-30 min.
[0013] A perovskite light transmission layer obtained according to the method for preparing a perovskite light transmission layer based on TPD small molecules.
[0014] A method for preparing a perovskite battery device comprises the following steps: S1, cleaning substrate; S2, prepare NiO hole transport layer on substrate x base substrate; S3, in NiO x A TPD film and a perovskite light transmission layer are prepared on a substrate according to the method for preparing a perovskite light transmission layer based on TPD small molecules; S4, after the perovskite light transmission layer cools to room temperature, a perovskite light modification layer is prepared on the perovskite light transmission layer using a PEAI solution; S5, after the perovskite photomodified layer cools to room temperature, an electron transport layer is prepared on its surface; S6, preparing a bathocuproin BCP blocking layer on the electron transport layer; S7, evaporating a silver electrode on the bathocuproin BCP barrier layer to obtain a perovskite battery device.
[0015] A perovskite battery device obtained according to the preparation method of the perovskite battery device.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing a perovskite light transmission layer based on TPD small molecules, wherein the V of the perovskite solar cell is increased by using the small molecule N,N′-diphenyl-N,N′-di(3-methylphenyl)-1,1′-biphenyl-4,4′-diamine (TPD). OC The lower trap density at the TPD / perovskite interface improves the PCE and stability of perovskite solar cells.
[0017] The present invention provides a method for preparing a perovskite battery device in NiO x The TPD hole transport layer is added at the interface of the NiO / perovskite film to effectively solve the x / perovskite interface, and energy level mismatch. x The defects or impurities at the interface of the perovskite film will affect the migration and recombination process of carriers, and adding a TPD hole transport layer can effectively reduce interface defects, thereby reducing interface recombination; and adding a TPD hole transport layer can improve the valence band and conduction band, which is more conducive to the extraction of holes and inhibits the transmission of electrons, thereby solving the problem of energy level mismatch and effectively improving its photoelectric conversion efficiency and stability.
[0018] TPD has the characteristics of hydrophobicity, low-temperature processing, and low price. Its hydrophobic characteristics make the device more stable. Compared with the high price of VNPB (2,800 yuan / gram), the price of TPD is as low as 150 yuan / gram. Finally, the photoelectric conversion performance of the device is significantly improved. The present invention provides an effective design idea and method for preparing perovskite solar cells with low cost, simple process, high efficiency and stability.
[0019] In the preparation of inorganic NiO x When sputtering on a high-thickness (HTL) substrate using an electron beam device, TPD effectively matches the energy level of the NiOx / perovskite interface, which is beneficial to the preparation of large-area inverse perovskite cell devices. Its low cost, simple preparation process, excellent photoelectric performance and device efficiency will help promote perovskite solar cells towards commercial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of a method for preparing a perovskite light transmission layer based on TPD small molecules of the present invention; Figure 2 It is a flow chart of a method for preparing a perovskite light transmission layer based on TPD small molecules of the present invention; Figure 3 A schematic diagram of a method for preparing a perovskite battery device according to the present invention; Figure 4 This is a flow chart of a method for preparing a perovskite battery device of the present invention; Figure 5 This is an X-ray diffraction (XRD) comparison diagram of a perovskite film prepared by the method described in Example 3 of the present invention and a perovskite film without a hole transport layer (TPD) added; Figure 6 This is a surface scan of the perovskite film prepared by the method described in Example 3 of the present invention; Figure 7 This is a scan of the surface of the perovskite film without adding a hole transport layer (TPD); Figure 8 This is an atomic force microscope image of the surface of the perovskite film prepared by the method described in Example 3 of the present invention; Fig. 9 A surface atomic force microscope image of a perovskite film without a hole transport layer (TPD); Fig.10 This is a comparison diagram of the surface steady-state fluorescence of the perovskite film prepared by the method described in Example 3 of the present invention and the perovskite film without adding a hole transport layer (TPD); Fig.11 This is a comparison chart of the photoelectric conversion efficiency of the perovskite film prepared by the method described in Example 3 of the present invention and the perovskite film without adding a hole transport layer (TPD). DETAILED DESCRIPTION
[0021] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0022] The present invention discloses a method for preparing a perovskite light transmission layer based on TPD small molecules, referring to Figure 1 , including the following steps: S1, spin coating TPD small molecule solution to form a wet film, and then annealing the wet film for the first time to obtain a TPD film with a thickness of 3~8nm; wherein, the TPD small molecule solution is obtained by dissolving TPD powder (Yuriguangneng PLT302011TT-5g) in chlorobenzene, the TPD small molecule is N,N′-diphenyl-N,N′-di(3-methylphenyl)-1,1′-biphenyl-4,4′-diamine, and the concentration of the TPD small molecule solution is 1~4mg / ml; during the first annealing, the temperature is 100~150℃, and the time is 10~30min.
[0023] S2, spin coating the perovskite precursor solution on the TPD film, followed by a second annealing to obtain a perovskite light transmission layer with TPD small molecules.
[0024] The preparation method of the perovskite precursor solution is as follows: PbI2: (CH(NH2)2I+CsI) with a molar ratio of 1:1 is dissolved in a polar solvent mixed with DMSO / DMF, the mixed solution is sealed, and after sufficient dissolution, a clear perovskite precursor solution with a concentration of 0.8~1.7M is obtained. During spin coating, the volume of the added perovskite precursor solution is related to the area of the perovskite film by 9.6~11 μL / cm 2 .
[0025] During the second annealing, the temperature is 100~150℃ and the time is 15~30min.
[0026] The present invention also discloses a perovskite light transmission layer obtained according to the preparation method of the perovskite light transmission layer based on TPD small molecules.
[0027] The present invention also discloses a method for preparing a perovskite battery device, referring to Figure 2 , including the following steps: S1, cleaning the substrate; specifically, selecting fluorine-doped SnO2 (FTO) transparent conductive glass and sequentially using acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, drying, and ultraviolet ozone for 5 to 10 minutes to remove surface organic impurities and increase the hydrophilicity of the FTO surface; S2, prepare NiO hole transport layer on substrate x Base substrate; specifically, NiO x The particles of the material are sputtered onto the surface of the cleaned FTO substrate using an electron beam device and exposed to ultraviolet ozone for 5 to 10 minutes.
[0028] S3, in NiO x A TPD film and a perovskite light transmission layer are prepared on a substrate according to a method for preparing a perovskite light transmission layer based on TPD small molecules; S4, after the temperature of the perovskite light transmission layer drops to room temperature, a perovskite light modification layer is prepared on the perovskite light transmission layer using a PEAI solution; specifically, PEAI powder is dissolved in isopropanol to obtain a PEAI solution with a concentration of 2 mg / mL, the PEAI solution is spin-coated on the perovskite substrate, and annealed at 110°C for 3 minutes to obtain a 2-5 nm perovskite light modification layer.
[0029] S5, after the perovskite light-modified layer cools to room temperature, an electron transport layer is prepared on its surface; specifically, the PCBM solution is spin-coated on the surface of the perovskite light-absorbing layer, and the relationship between the volume of the added PCBM solution and the area of the perovskite light-absorbing layer is 8-9.6 μL / cm 2 , forming an electron transport layer; the PCBM solution is a PCBM chlorobenzene solution.
[0030] S6, preparing a bathocuproin BCP blocking layer on the electron transport layer; specifically, spin coating or vapor deposition of the BCP solution on the surface of the electron transport layer to form a 3-8 nm blocking layer, and the solvent of the BCP solution is isopropanol.
[0031] S7, evaporating 80~120 nm silver electrode on the bathocuproin BCP barrier layer to obtain a perovskite cell device.
[0032] The present invention also discloses a perovskite battery device obtained according to the preparation method of the perovskite battery device. At room temperature, the light intensity of the solar simulator is increased to 100 mW / cm 2 (AM 1.5G), the efficiency of the perovskite battery device was tested, and a perovskite battery device with an efficiency PCE of 24.4%~25.18%, an opening voltage Voc of 1.14V~1.17V, and a fill factor FF of 80%~85% was obtained.
[0033] Example 1 S1, cleaning FTO glass substrate: select fluorine-doped SnO2 (FTO) transparent conductive glass (2.5*2.5 cm 2 ), wipe off the surface impurities with dust-free paper, then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with UV ozone for 10 minutes; S2, NiO x The particles of the material are sputtered onto the surface of the FTO substrate treated in step 1 by an electron beam device, and then exposed to ultraviolet ozone for 5 to 10 minutes.
[0034] S3, spin-coat the TPD solution on NiO x The film was annealed at 120 °C for 8 min.
[0035] Dissolve PbI2:(CH(NH2)2I+CsI) in a DMSO / DMF mixed solvent at a molar ratio of 1:1; seal the mixed solution, stir it thoroughly, and filter it to obtain a clear perovskite solution for later use; The perovskite precursor solution was uniformly coated on the surface of the TPD substrate. The perovskite wet film was obtained by spin coating and then placed on a 100°C hot plate for 30 minutes to obtain a perovskite light transmission layer. The relationship between the volume of the added perovskite precursor solution and the area of the perovskite film was 11 μL / cm 2 .
[0036] S4, after the annealed perovskite film cools to room temperature, the PEAI solution is spin-coated on the perovskite light transmission layer, and annealed at 110° C. for 3 minutes to obtain the perovskite light modification layer.
[0037] S5, the annealed perovskite light-modified layer is cooled to room temperature, and the PCBM chlorobenzene solution is spin-coated on the perovskite substrate to obtain an electron transport layer. The relationship between the volume of the added PCBM solution and the area of the perovskite light absorption layer is 8 μL / cm 2 .
[0038] S6, spin coating the BCP solution on the surface of the PCBM layer to obtain a barrier layer with a thickness of 3 nm.
[0039] S7, Ag electrode evaporation: The prepared film was transferred into the evaporation chamber and 80 nm thick Ag electrode was deposited by thermal evaporation. The effective area of the mask was 0.09 cm 2 .
[0040] The photoelectric conversion efficiency of the cell device prepared in Example 1 was tested by using a Keithley 2400 solar simulator at room temperature with a light intensity of 100 mW / cm 2 The battery efficiency was tested under (AM 1.5G) conditions with a voltage sweep range of 1.5 V to -0.1 V and -0.1 V to 1.5 V.
[0041] Example 2 S1, cleaning FTO glass substrate: select fluorine-doped SnO2 (FTO) transparent conductive glass (2.5*2.5 cm 2 ), wipe off the surface impurities with dust-free paper, then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with UV ozone for 15 minutes; S2, NiO x The particles of the material are sputtered onto the surface of the S1-treated FTO substrate using an electron beam device in ultraviolet ozone for 5 to 10 minutes.
[0042] Spin-coat the TPD solution onto NiO x The film was annealed at 110 °C for 10 min.
[0043] Dissolve PbI2:CH(NH2)2I:CsI in a DMSO / DMF mixed solvent at a molar ratio of 1:0.98:0.02; seal the mixed solution, stir it thoroughly, and filter it to obtain a clear perovskite solution for later use; The perovskite precursor solution was uniformly coated on the surface of the TPD substrate; the perovskite wet film was obtained by spin coating and then placed on a 120°C hot plate for 30 minutes to obtain a perovskite film. The relationship between the volume of the added perovskite precursor solution and the area of the perovskite film was 9.6 μL / cm 2 .
[0044] S4, after the annealed perovskite film cools to room temperature, (PEAI) is spin-coated on the perovskite substrate and annealed at 110° C. for 3 minutes to obtain a perovskite photomodification layer.
[0045] S5, the annealed perovskite light-modified layer was cooled to room temperature, and the PCBM chlorobenzene solution was spin-coated on the perovskite substrate to obtain an electron transport layer. The relationship between the volume of the added PCBM solution and the area of the perovskite light absorption layer was 9.6 μL / cm 2 .
[0046] S6, vacuum thermal evaporating the BCP solution onto the PCBM surface to obtain a BCP barrier layer with a thickness of 8 nm.
[0047] S7: The prepared film was transferred into the evaporation chamber and a 100 nm thick Ag electrode was deposited using thermal evaporation. The effective area of the mask was 0.09 cm 2 .
[0048] The photoelectric conversion efficiency of the cell device prepared in the example was tested: at room temperature, a Keithley 2400 solar simulator was used at a light intensity of 100 mW / cm 2 The battery efficiency was tested under (AM 1.5G) conditions with a voltage sweep range of 1.5 V to -0.1 V and -0.1 V to 1.5 V.
[0049] Example 3 S1, cleaning FTO glass substrate: select fluorine-doped SnO2 (FTO) transparent conductive glass (2.5*2.5 cm 2 ), wipe off the surface impurities with dust-free paper, then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with UV ozone for 12 minutes; S2, NiO x The particles of the material are sputtered onto the surface of the FTO substrate treated in step 1 by an electron beam device, and then exposed to ultraviolet ozone for 5 to 10 minutes.
[0050] Spin-coat the TPD solution onto NiO x The film was annealed at 100 °C for 10 min.
[0051] Dissolve PbI2:(CH(NH2)2I+CsI) in a DMSO / DMF mixed solvent at a molar ratio of 1:1; seal the mixed solution, stir it thoroughly, and filter it to obtain a clear perovskite solution for later use; The perovskite precursor solution was uniformly coated on the surface of the TPD substrate. The wet perovskite film was obtained by spin coating and then placed on a 150°C hot plate for 15 minutes to obtain a perovskite film. The relationship between the volume of the added perovskite precursor solution and the area of the perovskite film was 10 μL / cm2 .
[0052] S4, after the annealed perovskite film cools to room temperature, (PEAI) is spin-coated on the perovskite substrate and annealed at 110° C. for 3 minutes to obtain a perovskite photomodification layer.
[0053] S5, the annealed perovskite light-modified layer is cooled to room temperature, and the PCBM chlorobenzene solution is spin-coated on the perovskite substrate to obtain an electron transport layer. The relationship between the volume of the added PCBM solution and the area of the perovskite light absorption layer is 9 μL / cm 2 .
[0054] S6, spin coating the BCP solution on the surface of the PCBM layer to obtain a barrier layer with a thickness of 5 nm.
[0055] S7, Ag electrode evaporation: The prepared film was transferred into the evaporation chamber and a 120 nm thick Ag electrode was deposited using thermal evaporation. The effective area of the mask was 0.09 cm 2 .
[0056] The photoelectric conversion efficiency of the cell device obtained in Example 3 was tested by using a Keithley 2400 solar simulator at room temperature with a light intensity of 100 mW / cm 2 The battery efficiency was tested under (AM 1.5G) conditions, and a perovskite battery device with an efficiency PCE of 24.4%~25.18%, an opening voltage Voc of 1.14V~1.17V, and a fill factor FF of 80%~85% was obtained.
[0057] Comparative Example S1, cleaning FTO glass substrate: select fluorine-doped SnO2 (FTO) transparent conductive glass (2.5*2.5 cm 2 ), wipe off the surface impurities with dust-free paper, then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with UV ozone for 12 minutes; S2, NiO x The particles of the material are sputtered onto the surface of the FTO substrate treated in step 1 by an electron beam device, and then exposed to ultraviolet ozone for 5 to 10 minutes.
[0058] S3, after the annealed perovskite film cools to room temperature, (PEAI) is spin-coated on the perovskite substrate and annealed at 110°C for 3 minutes to obtain a perovskite light-modified layer.
[0059] S4, the annealed perovskite light-modified layer was cooled to room temperature, and the PCBM chlorobenzene solution was spin-coated on the perovskite substrate to obtain an electron transport layer. The relationship between the volume of the added PCBM solution and the area of the perovskite light absorption layer was 9 μL / cm 2 .
[0060] S5, spin coating the BCP solution on the surface of the PCBM layer to obtain a barrier layer with a thickness of 5 nm.
[0061] S6, Ag electrode evaporation: The prepared film was transferred into the evaporation chamber and a 120 nm thick Ag electrode was deposited using thermal evaporation. The effective area of the mask was 0.09 cm 2 .
[0062] Figure 5 This is the X-ray diffraction pattern of the perovskite film before and after optimization. It can be seen from the figure that compared with the control group (CT), no new phase appears in the optimized (TPD) film.
[0063] Figure 6 , 7 These are scanning electron microscope images of the perovskite film before and after optimization. It can be seen from the figure that compared with the control group (CT), no new substances appear on the surface of the optimized (TPD) film.
[0064] Figure 8 , 9 These are atomic force microscope (AFM) images of the perovskite film before and after optimization. It can be seen from the figure that the surface roughness of the optimized (TPD) film is lower than that of the control group (CT).
[0065] Fig.10 This is the fluorescence spectrum of the perovskite film before and after optimization. It can be seen from the figure that compared with the control group (CT) device, the luminescence intensity of the optimized (TPD) device is lower, indicating that the TPD film is conducive to the transmission of holes from the perovskite layer to the hole transport layer (HTL).
[0066] Fig.11 The JV curves of battery devices prepared using perovskite films before and after optimization. It can be seen from the figure that compared with the control group (CT) device, the optimized (TPD) device achieved a higher photoelectric conversion efficiency.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.
Claims
1. A method for preparing a perovskite light transmission layer based on TPD small molecules, characterized in that: The following steps are involved: S1, spin coating TPD small molecule solution to form a wet film, and then annealing the wet film for the first time to obtain a TPD film; S2, spin coating the perovskite precursor solution on the TPD film, followed by a second annealing to obtain a perovskite light transmission layer with TPD small molecules.
2. The method for preparing a perovskite light transmission layer based on TPD small molecules according to claim 1, characterized in that: In S1, the TPD small molecule solution is obtained by dissolving TPD powder in chlorobenzene, wherein the TPD small molecule is N,N′-diphenyl-N,N′-di(3-methylphenyl)-1,1′-biphenyl-4,4′-diamine; and the concentration of the TPD small molecule solution is 1-4 mg / ml.
3. The method for preparing a perovskite light transmission layer based on TPD small molecules according to claim 1, characterized in that: In S1, during the first annealing, the temperature is 100~150℃ and the time is 10~30min.
4. The method for preparing a perovskite light transmission layer based on TPD small molecules according to claim 1, characterized in that: In S1, the thickness of the TPD hole transport layer is 3~8nm.
5. The method for preparing a perovskite light transmission layer based on TPD small molecules according to claim 1, characterized in that: In S2, the perovskite precursor solution is prepared by dissolving PbI2: (CH(NH2)2I+CsI) with a molar ratio of 1:1 in a polar solvent mixed with DMSO / DMF, sealing the mixed solution, and obtaining a clear perovskite precursor solution with a concentration of 0.8~1.7M after sufficient dissolution.
6. The method for preparing a perovskite light transmission layer based on TPD small molecules according to claim 1, characterized in that: In S2, during spin coating, the relationship between the volume of the added perovskite precursor solution and the perovskite film area is 9.6~11 μL / cm 2 .
7. The method for preparing a perovskite light transmission layer based on TPD small molecules according to claim 1, characterized in that: In S2, during the second annealing, the temperature is 100~150℃ and the time is 15~30min.
8. A perovskite light transmission layer obtained by the method for preparing a perovskite light transmission layer based on TPD small molecules according to any one of claims 1 to 7.
9. A method for preparing a perovskite battery device, characterized in that: The following steps are involved: S1, cleaning substrate; S2, prepare NiO hole transport layer on substrate x base substrate; S3, in NiO x A TPD film and a perovskite light transmission layer are prepared on a substrate according to the method for preparing a perovskite light transmission layer based on TPD small molecules; S4, after the perovskite light transmission layer cools to room temperature, a PEAI solution is used to prepare a perovskite light modification layer on the perovskite light transmission layer; S5, after the perovskite photomodified layer cools to room temperature, an electron transport layer is prepared on its surface; S6, preparing a bathocuproin BCP blocking layer on the electron transport layer; S7, evaporating a silver electrode on the bathocuproin BCP barrier layer to obtain a perovskite battery device.
10. A perovskite battery device obtained by the method for preparing a perovskite battery device according to claim 9.
Citation Information
Patent Citations
Method for modifying hole extraction interface in inverted perovskite solar cell and application thereof
CN114975795A
Preparation method of blue-light perovskite quantum dot-based luminescent material and electroluminescent device of blue-light perovskite quantum dot-based luminescent material
CN116769479A